Peripheral Interventions Radiation Exposure Reduction Using a Sensor-Based Navigation System: A Proof-of-Concept Study - Philippe L. L’Allier, MD; Louis-Philippe Richer, PhD; Luke C. McSpadden, PhD; Jean-François Dorval, MD (CJC Open, 2022)
Background: Intravascular catheter positioning is done with radiography imaging. Increasing evidence indicates excessive ionizing radiation exposure for patients and physicians during catheterization procedures, making solutions to reduce radiation exposure a priority. This study evaluated the feasibility and impact of using sensor-based magnetic navigation on (i) fluoroscopy time and (ii) positioning accuracy and safety of a peripheral angioplasty balloon catheter. Methods: All patients (n = 10) underwent a balloon-positioning protocol using 2 navigation methods sequentially: (i) magnetic navigation with minimal fluoroscopy; (ii) fluoroscopic navigation. The navigation method order was randomized, and 4 consecutive placements per method were performed. A target vascular bifurcation was used as a fiduciary landmark for both methods to determine accuracy. Results: Balloon placements were successful with both navigation methods in all subjects, and no adverse events occurred. Magnetic guidance led to significant reductions in fluoroscopy time (0.37 ± 1.5 vs 15.0 ± 8.1 seconds, P < 0.001) and dose (0.3 ± 1.2 vs 24.1 ± 23.8 μGy.m2, P < 0.01). The time duration for balloon alignment was similar for the 2 navigation methods (4.8 ± 1.4 vs 4.8 ± 2.3 seconds, P = 0.89), and the accuracy was almost identical (0.51 ± 0.41 vs 0.51 ± 0.32 mm, P = 0.97). Conclusions: These results demonstrate the feasibility of using sensor-based magnetic guidance during simple peripheral interventional procedures; a significant reduction in ionizing radiation was achieved, with excellent positioning accuracy and safety. The clinical applications of magnetic guidance for device navigation during more complex percutaneous procedures should be evaluated. Résumé: Contexte: Le positionnement d’un cathéter intravasculaire fait appel à l’imagerie radiographique. De plus en plus de données probantes indiquent que les patients et les médecins subissent une surexposition aux rayonnements ionisants pendant le cathétérisme, ce qui fait des solutions de réduction de l’irradiation une priorité. Cette étude a permis d’évaluer la faisabilité du guidage magnétique par capteur et son effet sur (i) la durée de la fluoroscopie et (ii) la précision et la sécurité du positionnement d’un cathéter d’angioplastie périphérique à ballonnet. Méthodologie: Chez tous les patients (n = 10), le positionnement du ballonnet a été effectué en fonction d’un protocole fondé sur deux méthodes de guidage mises en œuvre séquentiellement : (i) guidage magnétique avec fluoroscopie minimale; (ii) guidage fluoroscopique. L’ordre dans lequel les méthodes de guidage ont été mises en œuvre a été randomisé, et quatre positionnements consécutifs par méthode ont été effectués. Une bifurcation vasculaire cible a servi de repère de fond de chambre afin de déterminer la précision des deux méthodes. Résultats: Les deux méthodes de guidage ont permis un positionnement adéquat du ballonnet chez tous les patients, et aucun événement indésirable n’est survenu. Le guidage magnétique a entraîné des réductions significatives de la durée de la fluoroscopie (0,37 ± 1,5 vs 15,0 ± 8,1 secondes, p < 0,001) et de la dose de rayonnement (0,3 ± 1,2 vs 24,1 ± 23,8 μGy.m2, p < 0,01). La durée de l’alignement du ballonnet était similaire lors de la mise en œuvre des deux méthodes de guidage (4,8 ± 1,4 vs 4,8 ± 2,3 secondes, p = 0,89), et la précision était presque identique (0,51 ± 0,41 vs 0,51 ± 0,32 mm, p = 0,97). Conclusions: Ces résultats démontrent la faisabilité du guidage magnétique par capteur dans le cadre d’angioplasties périphériques simples. L’exposition aux rayonnements ionisants a été réduite de façon significative, et la précision ainsi que la sécurité du positionnement se sont avérées excellentes. Les applications cliniques du guidage magnétique dans le contexte d’interventions percutanées plus complexes représentent une avenue de recherche à explorer.